ECG encryption enhancement with multi-layers of AES and DNA computing - Kh-Madhloom, Jamal (2023)
The Internet of Things (IoT), which is defined as a network of interconnected computing devices, mechanical and digital machines, and objects with unique identifiers (UIDs), which are able to transmit data across a network without requiring human-to-human or human-to-computer interactions, is currently a hot topic in the scientific community. This is due to the fact that IoT is defined as a network of interconnected computing devices, mechanical and digital machines, and objects with UIDs. IoT study fields currently involve security and privacy due to the fact that the installation of Cryptographic Internet Communications "ICs" for protected IC applications like Fog Computing and Cloud Computing devices is extremely crucial in any developing technology. Devices that use the internet of things for DNA sequence testing also require a high level of expertise in the application of public-key cryptography. Using brute force techniques, it is possible, in theory, to decipher any key if one has sufficient processing capacity. In order to more effectively incorporate both present technology and developing technology, models of DNA cryptography need to be developed. MATLAB 2017b, a reliable simulation method, was utilised throughout the construction and validation of the algorithm. The performance of the recommended approach makes it possible to thwart an attack using brute force considerably more fast than is possible with the encryption technologies that are currently in use. Evaluations of algorithms reveal that the proposed algorithm has achieved a level of security and complexity that is 48 times superior to that of other methods that have been tried and tested. The solution that has been suggested is one that is both secure and effective when it is put to use in conjunction with the ECG and Covid-19 image encoding algorithms. A reference electrocardiogram (ECG) signal as well as the Covid-19 image dataset were utilised in the validation and analysis of the recommended method. The pairing-based encryption known as "DNA sequence Enhanced Advanced Encryption Standard (EAES)" can be used to protect medical ECG signals that are stored in the cloud for healthcare purposes using the nebula network architecture. The proposed method indicates the feasibility of constructing such a dependable DNA sequence system in such a manner that it can be applied and integrated with either the biological environment or on DNA computers. This possibility is demonstrated by the fact that this system can be built. The proposed model is able to protect the DNA sequence stored in the Fog Computing cloud from plain text attacks by generating (I) the main key, which is the key to the EAES encryption algorithm, (II) the rule 1 key, which represents the DNA base number of possible key probabilities, and (III) the rule 2 key, which represents the number of binding probabilities for the DNA helical structure. These three keys are referred to collectively as the EAES encryption key. The construction of this key prioritises the highest possible level of safety.